A Critical Stylistic Analysis of the Ideological Positioning in Some Selected Poems by John Donne (Journal of the College of Languages (JCL), 2018)
This paper deals with the ideological positioning of the English poet John Donne in a selected poems of his i.e Holy Sonnet X, as regards the theme of death found therein. The researchers adopt an emerging branch of stylistics, called Critical Stylistics, as proposed by Jeffries (2010) in order to uncover the ideologies of the author regarding the topic concerned and how linguistic choices are used to slant ideas. The model is comprised of ten tools of analysis which, upon being applied to the selected data, have shown how the poet exploits language resources in order to pass his ideology and influence his readers. In this paper, the workings of only one tool are presented as applied to a certain portion of the data.